HUBUNGAN KELAHIRAN KEMBAR DENGAN KEMATIAN NEONATAL DI INDONESIA: ANALISIS DATA SDKI 2012 - Sarinah Bintang; Syahrizal Syarif; Helda Helda; Nikson Sitorus (Puslitbang Upaya Kesehatan Masyarakat, 2018)
Background: Neonatal Mortality Rate (NMR) is one indicator of the Sustainable Development Goals (SDGs) and contributes to the infant mortality rate. Twin birth is one of the risk factors for neonatal death, 6 times compared to single birth. The possibility of an increase in twin birth rates, and the high risk posed, could contribute negatively to efforts to reduce neonatal deaths in Indonesia.Objective: This study aims to determine the proportion of twin births, also analyzing association of twin birth with neonatal mortalityMethod: This study used the 2012 Indonesian Health Demographic Survey (IDHS), a cross-sectional designs that covers all provinces. The population was all children born alive in 2007-2012 from women of childbearing age who met the inclusion and exclusion criteria. The study sample was 15,083 live births. Result: The twin births rate in Indonesia by 14 per 1,000 births, increased from previous study 7,2 per 1.000 births in 1997-2007. There was significant association between twin births with neonatal mortality (POR 2,39; 95% CI 1,43-4,01; p-value 0,00), after controlled parity and birth weight. Conclusion: The proportion of twin births in Indonesia has increased almost doubled. Twins is high risk of neonatal death because they are born with low birth weight.